Self-Representation And Other-Representation In Algerian Secondary School Textbooks: A Critical Visual Analysis - Nabila YOUSFI (Akofena)
Abstract: This article represents an overall reading of the ways English textbooks in Algeria operate as tools to establish social hierarchies and asymmetrical power structures. These structures are represented through semiotic modes incorporated in textbooks’ materials. This work aims at identifying these visual semiotic modes, investigating how they express the native and target cultures, and determining the possible implications of theses representations on the Algerian pupil. This study adopted a qualitative research design, wherein Kress and van Leeuwen’s (2006) system of visual modality analysis was employed to study how self-representation and other-representation are portrayed in Algerian secondary school English textbooks. The samples selected for the analysis were extracted from the textbooks of all the three secondary levels. The findings obtained show the disparity existing between the way the self and the other are represented. Self-representational pieces are portrayed negatively whereas other-representational materials are depicted positively, which may influence the way pupils perceive culture-related topics.